Analysis of The Effect of Leadership Style and Employee Work Motivation on Service Effectiveness Mediated by Compensation - Akhmad Muzaky; Adya Hermawati; Sodik (Journal of Management Research and Studies, 2026)
The effectiveness of the Pasuruan City Social Service is a very important factor in efforts to improve community welfare. However, various factors such as leadership style, work motivation, and compensation are thought to influence the effectiveness of these services. Therefore, this study aims to analyze the influence of leadership style and employee work motivation on the effectiveness of compensation-mediated services. The population that is the focus of this study is all employees of the Pasuruan City Social Service, totaling 41 people. Given the relatively small population, which is 41 people, the sampling technique used is a saturated sample or census. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS software version 4. The results of the study showed that leadership style did not have a direct effect on service effectiveness. Work motivation did not have a direct effect on service effectiveness. Leadership style had a direct effect on compensation. Work motivation had a direct effect on compensation. Compensation had a direct effect on service effectiveness. Leadership style had an effect on service effectiveness through compensation mediation. Work motivation had an effect on service effectiveness through compensation mediation.